Optimization of the Diagnosis and Treatment of Oral Epulis Based on Morphological and Cytological Analysis (Texas Journal of Medical Science, 2022)
The experience of complex treatment of 200 patients aged 20 to 50 years in the Bukhara region on the structure of oral morbidity is presented. The studied patients were under the control of a dentist for a calendar year. The patients were between the ages of 20 and 50, of which 74 were men and 126 were women. All patients applied to the dental clinic for epulis in the oral cavity. After complex treatment with the use of MIL radiation, the main group of patients did not have a relapse, which showed significant advantages over traditional methods of treating epulis in the first group of patients.